Mechanistic approach to electrochemical processes in the passive and pitting corrosion regions of carbon steel in dilute NaOH solutions containing Na2SO4 - Salvarezza, Roberto Carlos (1987)
Passive film growth, electrodissolution and pitting corrosion of prepassivated carbon steel in dilute NaOH solutions containing Na2SO4 are studied by using potentiostatic and potentiodynamic techniques. Two kinetic reaction models implying different passive film growth mechanisms are proposed to describe the passive film growth, the electrodissolution process through the passive film and pitting corrosion. Current transients at constant potential recorded in the passive and pitting region can be satisfactorily reproduced by assuming the occurrence of simultaneous processes. The physical interpretation of adjusting parameters derived from the two models is consistent with a duplex structure for the passive film and with the nucleation and growth of pits when the applied potential exceeds the breakdown potential although both mechanisms for the passive layer growth seem to be equally probable.